1998
DOI: 10.1093/geronb/53b.1.p4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Positive and Negative Social Exchanges with Various Sources on Depressive Symptoms in Younger and Older Adults

Abstract: Addressing a previous gap in the gerontological literature, the present study examined the effects of both positive and negative social exchanges within key relationships (spouse, children, and other relatives/friends) on the depressive symptoms of younger (28 to 59 years old) and older (60 to 92 years old) men and women. Separate analyses were carried out on younger adults (N = 452) and older adults (N = 849) who were respondents in the Americans' Changing Lives study. In both age groups, positive and negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
238
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(264 citation statements)
references
References 80 publications
19
238
0
2
Order By: Relevance
“…Namely, consistent with certain under-explored threads in research on social support and psychological well-being [20,21], the greatest effects on the mental health outcomes were observed in the negative support domain, particularly with regard to suicidal ideation -an especially dangerous manifestation of psychological distress. Specifically, feelings of being exploited, rejected, and emotionally distant from family members played heavily into experiences of depression and suicidal ideation.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Namely, consistent with certain under-explored threads in research on social support and psychological well-being [20,21], the greatest effects on the mental health outcomes were observed in the negative support domain, particularly with regard to suicidal ideation -an especially dangerous manifestation of psychological distress. Specifically, feelings of being exploited, rejected, and emotionally distant from family members played heavily into experiences of depression and suicidal ideation.…”
Section: Discussionsupporting
confidence: 60%
“…Such negative social interactions constitute a distinct dimension of social support, with separate and potentially deleterious impacts on mental health [20][21][22]. Importantly, sustained interpersonal strains tend to be more characteristic of relationships with family than with non-related peers, as friendships high in unsupportive elements are generally less likely to be maintained relative to the more obligatory bonds of family [23].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been demonstrated that associations between received support and depression were different for young and old individuals depending on the source of support (Okun and Keith 1998). Sources of support in this study were partner, children, and other relatives/friends.…”
Section: Age Differences Of Social Supportmentioning
confidence: 63%
“…Prior investigators have used these items to measure negative interactions (e.g., Krause, 1995;Okabayashi et al, 2004;Okun & Keith, 1998).…”
Section: Variables and Measuresmentioning
confidence: 99%
“…Chinese elderly; social support; negative interactions; mental health; heterogeneity in old age Social relationships have positive ("social support," e.g., emotional and instrumental support) and negative aspects ("negative interactions," e.g., criticism and demand), and both are related to older adults' well-being (Ingersoll-Dayton, Morgan, & Antonucci, 1997;Newsom, Nishishiba, Morgan, & Rook, 2003;Okun & Keith, 1998). However, few studies are based on data from developing nations.…”
Section: Introductionmentioning
confidence: 99%